PIDANA MATI CARA TERBAIK UNTUK MEMPERTAHANKAN PENEGAKAN HUKUM SEBAGAI ULTIMUM REMEDIUM KEJAHATAN NARKOTIKA - James Ricardo Farida; RAS, Hernawati (Wacana Paramarta: Jurnal Ilmu Hukum, 2024)
This research focuses on how the death penalty is implemented as a final means of enforcing criminal punishment for drug crimes. This research uses empirical juridical law. The death penalty given to narcotics crime perpetrators, especially producers, both dealers and dealers, is very appropriate, this is in accordance with the absolute theory, the theory of funding. According to this theory, punishment is justified because someone has committed a criminal act, so that the criminal must absolutely accept criminal retribution without considering how the punishment impacts the convict. The absolute theory approach says that there is a right to impose harsh penalties and that because a person is responsible for his actions, he should accept the punishment given. This shows that the essence of the absolute approach is a feeling of revenge towards the perpetrator. In other words, the justification lies in the crime itself. Among the methods of punishment, capital punishment or punishment is the best option. However, if an act is deemed to be truly detrimental to the state and the people, such as narcotics crimes, the state must use the death penalty as the main option.